Optimizing the Performance of Women and Child Protection Unit Investigators in Handling Violent Criminal Actions Against Women and Children at Kendal Polres - Fernanda, Laura Agelia (Advances in Police Science Research Journal, 2024)
This research is motivated by the high number of violence against women and children that occurs in the jurisdiction of Kendal Polres, although efforts have been made but the results are still not optimal, there are several main problems in this study, namely regarding existing and ongoing investigations and inquiries in handling criminal acts of violence against women and children and problem solving steps to optimize the performance of the PPA Unit of Kendal Police Criminal Investigation Unit in handling criminal acts of violence against women and children. The findings show that the performance of the PPA in handling criminal acts of violence against women and children is not optimal, seen from the SWOT analysis conducted that the weaknesses in the PPA unit are aspects of human resources that still have limitations in terms of competence, especially those related to handling victims of women and children. Then the PPA has a challenge where the PPA Unit itself still lacks human resources. Furthermore, the capacity of members to absorb the existing budget to support the performance of members is still inadequate. Based on the research carried out, the author provides suggestions, namely the need for an increase in the quantity of PPA Unit staff at Kendal Police Criminal Investigation, the need for vocational training or education to improve the quality of performance of PPA Unit investigators, and the need for exceptional improvements to service rooms and room completeness according to regulatory standards.